Дослідження великої рогатої худоби червоної польської породи за генами капа-казеїну (CSN3) та бета-лактоглобуліну (BLG) - Подоба, Ю.В.; Ящук, Т.С.; Добрянська, М.Л.; Березовський, О.В.; Джус, П.П.; Копилов, К.В.; Копилова, К.В.; Сидоренко, О.В. (Фактори експериментальної еволюції організмів, 2013)
Aim. To study the genetic structure of populations of cattle Polish Red breed genes for kappa-casein and beta-lactoglobulin. Methods. Identification of individual genotypes of animals studied breed was performed by PCR-RFLP analysis. Results. Investigated populations were characterized by high frequency of desired alleles A for gene CSN3 and B for gene BLG. Conclusions. For Red Polish breed found significant genetic potential for milk production indices.